2001
DOI: 10.1046/j.1471-4159.2001.00193.x
|View full text |Cite
|
Sign up to set email alerts
|

Axonal transport of VR1 capsaicin receptor mRNA in primary afferents and its participation in inflammation‐induced increase in capsaicin sensitivity

Abstract: Capsaicin receptors are expressed in primary sensory neurons and excited by heat and protons. We examined the in¯ammation-induced changes of the level of VR1 capsaicin receptor mRNA in sensory neurons and the sensitivity of primary afferents to capsaicin. Carrageenan treatment induced axonal transport of VR1 mRNA, but not that of preprotachykinin mRNA, from the dorsal root ganglia to central and peripheral axon terminals. The sensitivity of central terminals to capsaicin, which was estimated by measuring the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(88 citation statements)
references
References 31 publications
3
81
4
Order By: Relevance
“…These findings imply a potential role of TRPV1 in morphine tolerance and associated thermal hyperalgesia. Previous RT-PCR studies did not show an increase in TRPV1 mRNA levels in the DRG after carrageenan-or complete Freund's adjuvant-induced inflammation (Tohda et al, 2001;Ji et al, 2002, Endres-Becker et al, 2007. We also did not detect the increase in TRPV1 mRNA levels in the DRG of morphinetolerant animals.…”
Section: Discussioncontrasting
confidence: 88%
“…These findings imply a potential role of TRPV1 in morphine tolerance and associated thermal hyperalgesia. Previous RT-PCR studies did not show an increase in TRPV1 mRNA levels in the DRG after carrageenan-or complete Freund's adjuvant-induced inflammation (Tohda et al, 2001;Ji et al, 2002, Endres-Becker et al, 2007. We also did not detect the increase in TRPV1 mRNA levels in the DRG of morphinetolerant animals.…”
Section: Discussioncontrasting
confidence: 88%
“…Our data are very consistent with previous electrophysiological and gene knock-out studies of TRPV1 function (i.e., TRPV1 is required for peripheral sensitization to noxious thermal but not mechanical stimuli) (Caterina et al, 2000;Davis et al, 2000). The present study showed the upregulation in TRPV1 mRNA/protein in the uninjured DRG, although several studies have demonstrated an increase in the TRPV1 protein but not in its mRNA, after peripheral inflammation (Tohda et al, 2001;Ji et al, 2002). The reasons for this discrepancy are not clear, but other reports have shown that inflammation and/or NGF increased TRPV1 mRNA in adult DRG neurons (Winston et al, 2001;Amaya et al, 2003).…”
Section: Bdnf and Trpv1 Expression In Adjacent Intact L4 Drg Neurons supporting
confidence: 93%
“…Although the question of which signals activate TRPV1 in vivo remains a matter of debate, numerous studies imply the importance of spinal cord TRPV1 for pain processing. Indeed, the receptor is significantly upregulated in the dorsal horn during chronic inflammation (Tohda et al, 2001;Luo et al, 2004), and intrathecal administration of either selective TRPV1 antagonists or small interfering RNAs that target TRPV1 produced strong analgesic effects in animal models of inflammatory, neuropathic, and visceral pain (Kelly and Chapman, 2002;Kanai et al, 2005;Christoph et al, 2006). Moreover, significant CNS penetration of orally administered TRPV1 antagonists was required to attenuate pain mediated by central sensitization (Cui et al, 2006).…”
Section: Trpv1 Mediates Presynaptic Camentioning
confidence: 99%
“…At the peripheral terminals of primary nociceptors, TRPV1-mediated Ca 2ϩ influx triggers the release of neuropeptides, which contributes to the development of neurogenic inflammation (Caterina and Julius, 2001). TRPV1 is also found in the central processes of primary afferent neurons (Guo et al, 1999;Hwang et al, 2004), and its expression in the dorsal horn of the spinal cord is upregulated during chronic inflammation (Tohda et al, 2001;Luo et al, 2004). Notably, intrathecal administration of selective TRPV1 antagonists significantly reduces pain associated with inflammation and nerve injury (Kanai et al, 2005;Christoph et al, 2006;Cui et al, 2006).…”
mentioning
confidence: 99%